Pengaruh Pembelajaran Kewirausahaan Terhadap Minat Berwirausaha - Sev Rahmiyanti; Rohaelis Nuraisiah (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2019)
This research aims to know the entrepreneurial study of entrepreneurial interests (case studies on management students, accounting and computer science of Serang University). It is expected to be able give a benefit and illustrated, that entrepreneurial learning can affect the interest of entrepreneurial. To improve entrepreneurial interest in college students, lecturers are expected to be able to give entrepreneurial learning that will get the students interested in doing entrepreneurial activities. By entrepreneurial learning, students are encouraged and directed to be able to open up their knowledge of entrepreneurship. Entrepreneurship can potentially give a good life in current employment conditions. Object in this study are 126 students composed of management, accounting and computer science students. Research methods use the simple linear regression analysis to do data analysis. The studies have shown that entrepreneurial study give a positive impact on the entrepreneurial interest.